DHEA and non-alcoholic fat liver disease: increased gene expression of peroxisome proliferation-activated receptor γ (PPARγ) and fatty acid synthase (FAS) - Almeida, Felipe Natali (2014)
Dehydroespiandrosterone (DHEA) is associated with improvements in chronic degenerative diseases, including obesity, insulin resistance, and cardiovascular diseases. Nevertheless, it is observed an increase in its concentration in individuals with liver lipid infiltration, but it is not precise if this condition emerges as a cause or a consequence. In this way, we aimed to identify gene expression alterations in lipid and glucose liver metabolism markers, as well as oxidative stress markers. For this purpose, male Wistar rats, 12-14 months old were treated with subcutaneous injections of DHEA (only dose of 10 mg kg-1); and after 7 days, hepatic gene expression by PCR real time were performed for the following genes:  G6Pase, PEPCK, FAS, PPARγ, malic enzyme, ChREBP, LXR, catalase, GPx, iNOS, NADPH oxidase subunits and PCNA. We observed a tendency of reduction in G6Pase gene expression in treated group (p = 0.08). In addition, it was identified an increase in liver PPARγ and FAS gene expressions, two markers of increased activity of lipogenic pathway. We also observed an increase in iNOS gene expression, a known inductor of systemic and hepatic insulin resistance. In conclusion, our data indicates that the treatment with DHEA can be associated with the development of liver lipid infiltration and hepatic insulin resistance.